9150 [1950] - 1951 senelerinde Bulgaristandan tehcir edilen Türk göc̦menlerinden bir örnek grup sec̦ilerek dayanișma ve sosyal intibak bakimindan aile cesametinin ve aile ic̦indeki münasebetlerin araștirilmasi = . A study of the size of the family relations and solidarity in terms of social adjustment in a sample of Turkish Bulgarian Immigrants expelled from Bulgaria between 1950-1951 (Sermet, 1960)
Istanbul Üniversitesi Iktisat Fakültesi Mecmuasi 20(1959):no.1-4 den ayri basi.